Assessing soil functioning: What is the added value of soil organic carbon quality measurements alongside total organic carbon content? - Koorneef, Guusje J.; Pulleman, Mirjam M.; Comans, Rob N.J.; Rijssel, Sophie Q. van; Barré, Pierre; Baudin, François; Goede, Ron G.M. de (Elsevier, 2024)
Soil organic carbon (SOC) content is the most widely used soil health indicator, but many soil functions are also influenced by the quality of SOC. Yet, standardized SOC quality parameters that can be used in soil health assessments in addition to SOC content are still in development. Here, we investigated the relationships between various SOC parameters (both quantity and quality) and soil functions. We collected 223 soil samples from arable fields in two contrasting Dutch soil types i.e., marine clay and sand. For each sample, we assessed three soil functions (i.e., biological population regulation, element cycling, and soil structure and water regulation) by measuring five indicators per function. We also analyzed SOC quality with four techniques (C:N-ratio, POX-C, Rock-Eval, POM-MAOM fractionation), resulting in 21 SOC quality parameters, and measured SOC content. We then determined for each soil type how much variation in each function indicator was explained by the SOC parameters and other measured intrinsic soil properties. We found that SOC parameters and intrinsic soil properties explained at most 30 ± 22% of the variation in soil function indicators. SOC content explained 9 ± 16% of the variation across functions and soil types. Including one single SOC quality parameter alongside SOC content never had significant added value in explaining soil functions. Only including multiple Rock-Eval parameters alongside SOC content significantly increased the explained variation compared to SOC content alone, as well as combining multiple parameters from the four different SOC quality techniques. We conclude that the relationships between the SOC quality parameters and soil functions are insufficiently straight-forward to add significant explanatory power to SOC content alone. We recommend that before including SOC quality parameters in soil health monitoring, more emphasis should be put on evaluating their relation to soil functions and their potential redundancy when used alongside SOC content.